Towards Good Corporate Governance in South Africa: Private Enforcement versus Public Enforcement - Hendricks, Ebrahiem (Department of Commercial Law, 2014)
For the past six and half years a great deal of attention has been devoted to the reform of South African company law. The reform process commenced in September 2003, when the Department of Trade and Industry (DTI) initiated a reform programme that included a review of existing securities regulation and, of corporate structures and practices in the area of corporate governance. Subsequently, in March 2004 (and updated in June 2004) the DTI published a policy document on corporate law reform entitled 'South African Company Law for the 21st Century: Guidelines for Corporate Law Reform'. This policy paper explained that company law in South Africa would be reviewed and modernised. The objectives of the reform process were to align it with international trends and to accommodate the economic and legislative changes that have taken place in South Africa since the advent of democracy in 1994. The policy paper also explained that this reform process would occur in two stages. Firstly, urgent interim changes would be brought by the Corporate Law Amendment Act No 24 of 2006. The Act provided for, amongst others, assistance to acquire shares and greater protection of minority shareholders in respect of takeovers .The Act came into effect on 14 December 2007. Secondly, the new Companies Act will repeal and replace the entire Companies Act No 61 of 1973, when it becomes operational.